Evaluating Exercise Progression in an Australian Cardiac Rehabilitation Program: Should Cardiac Intervention, Age, or Physical Capacity Be Considered? - Price, Kym Joanne (Int J Environ Res Public Health, 2021)
Progression of prescribed exercise is important to facilitate attainment of optimal physical capacity during cardiac rehabilitation. However, it is not clear how often exercise is progressed or to what extent. This study evaluated whether exercise progression during clinical cardiac rehabilitation was different between cardiovascular treatment, age, or initial physical capacity. The prescribed exercise of sixty patients who completed 12 sessions of outpatient cardiac rehabilitation at a major Australian metropolitan hospital was evaluated. The prescribed aerobic exercise dose was progressed using intensity rather than duration, while repetitions and weight lifted were utilised to progress resistance training dose. Cardiovascular treatment or age did not influence exercise progression, while initial physical capacity and strength did. Aerobic exercise intensity relative to initial physical capacity was progressed from the first session to the last session for those with high (from mean (95%CI) 44.6% (42.2–47.0) to 68.3% (63.5–73.1); p < 0.001) and moderate physical capacity at admission (from 53.0% (50.7–55.3) to 76.3% (71.2–81.4); p < 0.001), but not in those with low physical capacity (from 67.3% (63.7–70.9) to 85.0% (73.7–96.2); p = 0.336). The initial prescription for those with low physical capacity was proportionately higher than for those with high capacity (p < 0.001). Exercise testing should be recommended in guidelines to facilitate appropriate exercise prescription and progression.